1987
DOI: 10.1254/jjp.43.253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the substance P antagonist spantide on adrenal sympathetic nerve activity in rats.

Abstract: Abstract-Inorder to elucidate the role of substance P in adrenal nerve activity, the effects of substance P antagonists on 1) tonic activity of the adrenal sympa thetic nerve, 2) the response to exogenous substance P and 3) cutaneo-adrenal nerve reflex were investigated in anesthetized rats. Substance P or its antagonist [(Arg', D-Trp7'9, Leu" )-substance P: spantide] was injected into the subara chnoid space via polyethylene tubing.Intrathecal administration of spantide (0.1 10 iig) produced a slight and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Spantide, [D-Arg', D-Trp7 9, Leu"] substance P. is one of the most potent tachykinin antagonists (Rosell et al, 1983;Folkers et al, 1984), and has often been used to examine possible neurotransmitter roles of tachykinins in peripheral and central nervous systems (Folkers et al, 1984;Fujino et al, 1987;Togashi et al, 1987;Otsuka & Yanagisawa, 1988;Barth6 et al, 1989). Several studies suggested that spantide is an antagonist with preference for NK1-tachykinin receptors (Chahl, 1985;Buck & Shatzer, 1988;Bartho et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Spantide, [D-Arg', D-Trp7 9, Leu"] substance P. is one of the most potent tachykinin antagonists (Rosell et al, 1983;Folkers et al, 1984), and has often been used to examine possible neurotransmitter roles of tachykinins in peripheral and central nervous systems (Folkers et al, 1984;Fujino et al, 1987;Togashi et al, 1987;Otsuka & Yanagisawa, 1988;Barth6 et al, 1989). Several studies suggested that spantide is an antagonist with preference for NK1-tachykinin receptors (Chahl, 1985;Buck & Shatzer, 1988;Bartho et al, 1989).…”
Section: Introductionmentioning
confidence: 99%